PATTERN OF ADVERSE DRUG REACTIONS IN A TERTIARY CARE TEACHING HOSPITAL: A CROSS-SECTIONAL STUDY - Raja, Sangeetha; R, Jamuna Rani; P, Kala (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The aim of this study was to carry out adverse drug reactions (ADRs) monitoring in various departments of a tertiary care teaching hospital. Methods: A cross-sectional study was conducted on ADRs reported in the hospital from December 2012 to May 2013 after obtaining Institutional Ethics Committee approval. Results: A total of 40 ADRs were reported, 47.50% were males and 52.50% were females. The female adult population was 45%. The majority of ADRs were due to antimicrobial agents especially beta-lactam antibiotics (42.5%) followed by NSAIDs (7.50%). A maximum number of patients (75%) were reported with dermatological manifestations. The department of medicine reported the highest number of ADRs (37.5%). As per Naranjo's probability scale, 62.5% reports were assessed as probable. 62.5% reports were documented as mild according to Modified Hartwig's criteria for severity assessment. Conclusion: This study was done to sensitize the practicing physicians on the importance of adverse drug monitoring and reporting. Keywords: Pharmacovigilance, Adverse drug reactions, Tertiary care teaching hospital, Antimicrobial agents.